2005
DOI: 10.1080/09286580500212904
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glaucoma in the Wroclaw Population. The Wroclaw Epidemiological Study

Abstract: The prevalence of the different types of glaucoma was similar to that found in other white populations. Among the subjects examined, 79 had various forms of glaucoma and 71% of them had not previously been diagnosed. Undiagnosed glaucoma is a serious public health problem in Poland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
2
37
2
2
Order By: Relevance
“…This hypothesis was supported by Alvarado et al, who reported elevated level of oxidative damage in glaucomatous TM cells in comparison to controls [17]. Nizankowska and Kacz- marek suggested that progressive neuronal death that is characteristic for glaucomatous optic nerve change may be associated with oxidative stress [18]. Our previous study supported the hypothesis that oxidative stress may play an important role in POAG development.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis was supported by Alvarado et al, who reported elevated level of oxidative damage in glaucomatous TM cells in comparison to controls [17]. Nizankowska and Kacz- marek suggested that progressive neuronal death that is characteristic for glaucomatous optic nerve change may be associated with oxidative stress [18]. Our previous study supported the hypothesis that oxidative stress may play an important role in POAG development.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for this investigation was that non-population-based public glaucoma screening is frequently organised in different communities, and recent data suggest that by combining different diagnostic methods and/or criteria, the accuracy and the positive likelihood ratio of the screening can be significantly increased. 13,14 However, as the prevalence of glaucoma in the adult Caucasian general population is far below the value optimal for screening, [2][3][4][5][6][7] it is very desirable to increase the prevalence of glaucoma among the self-recruited screening participants. 11,13 To specifically motivate persons to attend who have a high probability of having the disease, information on the risk factors for glaucoma needs to be provided when the screening event is publicised in the media.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of chronic open-angle glaucoma is approximately 1.5-3% in Caucasians over 40 years of age. [2][3][4][5][6][7] As chronic open-angle glaucoma develops without clinical symptoms, it frequently happens that progression to the stage of severe damage may occur before the patient becomes aware of the disease. Even in the developed countries, it is estimated that 50% of glaucoma sufferers remain undetected.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is the most common cause of blindness, and the leading cause of irreversible blindness worldwide [5,6]. Primary open angle glaucoma (POAG) is the most common type of glaucoma.…”
Section: Introductionmentioning
confidence: 99%